Sustainable and harmonious development of the personality in the context of implementation of the concept of pedagogical facilitation - Zagorulya Tatyana (E3S Web of Conferences, 2021)
In the article, the author presents the results of research on sustainable and harmonious development of personality in the context of implementation of the concept of pedagogical facilitation. The author's concept of pedagogical facilitation, based on K. Rogers’ theory, has been implemented over years at the Ural State University of Economics. In this article, the author considers her own experience of applying the methods of goal setting, which contribute to the sustainable and harmonious development of the personality. In the context of implementation of the concept of pedagogical facilitation, self-actualization of the individual is carried out, the life scenario is developed, in which priority goals, and ways of achieving them are identified. The obtained result of the study confirms that personal, professional and social goal setting is an important factor of sustainable and harmonious development of the personality in an unstable and constantly changing environment.